DETECTION OF PATHOGENICITY GENES ENCODING ABILITY TO TOXIGENESIS IN ESCHERICHIA COLI ISOLATED FROM THE CHILDREN INTESTINAL BIOTOPE - E. I. Ivanova; S. M. Popkova; Yu. P. Dzhioyev; E. B. Rakova (Acta Biomedica Scientifica, 2013)
Shiga toxins (stxs) are the virulence factor of enterohemorrhagic Escherichia coli (EHEC). Shiga toxin-producing Escherichia coli has been recognized as an important food-borne pathogen that causes severe diseases such as a hemolytic uremic syndrome (HUS). Provides information about the species composition of the major opportunistic organisms that inhabit this biotope. Using polymerase chain reaction (PCR) 96 strains of E. coli were examined for the presence of genes stx1 and stx2 coding the ability to toxigenesis. They were isolated from the children with functional disorders of the gastro-intestinal tract. Both pathogenicity genes present in the genome of E. coli with normal enzyme activity more often (stx1 in 24,2 % of genomes, stx2 in 9,1 %). The presence of stx1 and stx2 genes in different biochemical variants of E. coli allows to ascertain the fact of presence of a potentially pathogenicity reservoir in non-pathogenic forms of E. coli. Intestinal microflora is integral part of each individual. Further studying of its functions, the states interfering qualitative and quantitative composition of microorganisms, colonizing human gastrointestinal tract, as well as the pathogenic potential.